Changing epidemiology of genital herpes simplex virus infection in Melbourne, Australia, between 1980 and 2003. Issue 4 (4th August 2004) - Tran, T; Druce, J D; Catton, M C; Kelly, H; Birch, C J
Abstract : Objective: To investigate changes in the proportions of patients infected with genital herpes simplex virus (HSV) types 1 and 2 from 1980 to 2003 in Melbourne, Australia. Methods: A total of 25 372 patients were studied retrospectively. The proportions of HSV-1 and HSV-2 detected in these individuals were analysed by age, sex, and genital site. Results: In 1980 only 15.8% of HSV positive genital specimens were HSV-1 compared to 34.9% in 2003. In 2003 HSV-1 was detected in 77% of patients aged less than 20 years. Females were more likely to be infected with HSV-1, although the rate of increased detection was more pronounced in males. Except for females over the age of 40, the trend for the increase in HSV-1 was detected in all age groups. No specific genital site in either sex was associated with the increase. Conclusions: The proportion of genital HSV-1 has increased in Australian patients, although HSV-2 is still the most common cause of genital infection. Confirmation of HSV type is necessary for optimal patient management.